Uji Sitotoksisitas dan Proliferasi Senyawa 1-(4- Trifluorometilbenzoiloksimetil)-5-Fluorourasil terhadap Sel Kanker Payudara MCF-7 (Cytotoxicity and Proliferation Assay of 1-(4- Trifluoromethylbenzoyloxymethyl)-5-Fluorouracil) On MCF-7 Breast Cancer Cell - Puspita Arum Wijayanti; Ayik Rosita Puspaningtyas; Dian Agung Pangaribowo (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
1-(4-trifluoromethylbenzoyloxymethyl)-5-fluorouracil (TFU) is a derivative compound of anticancer agent, 5-fluorouracil (5-FU). TFU has been synthesized by Ernawati to increase the anticancer activity of 5-FU. However, the cytotoxic and antiproliferative effect of TFU had not been carried out. This study aimed to evaluate the cytotoxic and antiproliferative activity of TFU compared to 5-FU on MCF-7 breast cancer cell line using MTT method. The citotoxicity study was done for 24 hours. The antiproliferative study was done for 24, 48, and 72 hours. The cytotoxic effect was determined based on IC50 value while the antiproliferative effect was determine based on the doubling time value. The results showed that TFU had better cytotoxicity on MCF-7 with IC50 value 401.03 ± 0.370 µM compared to 5-FU with IC50 value 4216.32 ± 800.28 µM. The doubling time value of TFU at concentration of ½ IC50, IC50, and 1½ IC50 were 359.66; 364.39; and 448.40 hours respectively, while 5-FU were 184.45; 214.00; and 220.63 hours. The doubling time value indicated that TFU compound was able to prolong the doubling time of MCF-7 cell line compared to 5-FU. Keywords: cancer, cytotoxicity, proliferation,1-(4-trifluoromethylbenzoyloxymethyl)-5-fluorouracil, MCF-7